Analisis Penerapan Petty Policy oleh Amerika Serikat Melalui African Growth Opportunity Act dalam Kerja Sama Perdagangan Pakaian Bekas dengan East African Community - Annisa Annisa; Ika Riswanti Putranti (Journal of International Relations Diponegoro, 2020)
In 2015, countries united under organization named East African Community (EAC), declared will ban importation on second-hand clothes started in 2019. During EAC Summit which held on February 22nd, 2018, the leaders agreed to relocate their investment to local industries, and implementation of tariffs on second-hand clothes. Unfortunately, President Donald Trump threatened will remove aids given to the countries through African Growth Opportunity Act (AGOA), a regulation which eliminate trade tariffs. He also threatened Rwanda, as one of the ban initiator, by removing its membership from AGOA. However, from profit calculations, second-hand trade have little impacts for United States economy. This research will use decision making theory to explain the motives of US ‘threatening’ action to East African Community. This research use one of its concept, Rational Actor Model (RAM) to analyze further the reasons behind US petty action through the AGOA’s platform. The main argument of this reserach is US desicion is rational, motivated by two factors: to solve environmental problem caused by secondhand clothes and regaining political influence within East African region by securing the secondhand clothing trade with EAC.